PENGARUH PHYSICAL CAPITAL, HUMAN CAPITAL, DAN STRUCTURAL CAPITAL TERHADAP PROFITABILITAS, PRODUKTIVITAS DAN PENILAIAN PASAR PADA PERBANKAN INDONESIA (Studi kasus perbankan yang terdaftar di BEI Tahun 2008-2011) - Rahmadhani, Sari (STIE Totalwin Semarang, 2013)
This study aimed to examine the effect of disclosure of intangible assets in the banking company. Disclosure of intangible assets is an important concern for modern accounting disclosures aimed determine the ability of an intangible asset in improving profitability, productivity and market valuation. New types of intangibles such as employee competence, relationships with customers, simulation models, administration and computer systems are not recognized in the financial reporting model and conventional management. Testing of intangible assets is done by using the components of capital, namely Physical Intellectual Capital, Human Capital, Structural Capital.This research was conducted by a quantitative method using secondary data. The population of this study was obtained from the banks listed on the Indonesia Stock Exchange in the period 2008 - 2011. The study sample was 12 Banks are selected using purposive sampling method. Analysis techniques used is by using multiple linear regression model using SPSS. The results showed results provide empirical evidence that the Physical capital does not affect the profitability, productivity, and penilaiaan banking market in Indonesia. While human capital affect the profitability and market penilaiaan, but has no effect on the pebankan produkivitas. Structural capital does not affect the profitability and market penilaiaan, but the effect on the productivity of banking in Indonesia.